Sterol Regulatory Element-Binding Protein (Sre1) Promotes the Synthesis of Carotenoids and Sterols in Xanthophyllomyces dendrorhous - Gutiérrez, María Soledad; Campusano, Sebastián; González, Ana María; Gómez, Melissa; Barahona, Salvador; Sepúlveda, Dionisia; Espenshade, Peter J.; Fernández-Lobato, María; Baeza, Marcelo; Cifuentes, Víctor; Alcaíno, Jennifer (Frontiers in Microbiology, 2019)
Xanthophyllomyces dendrorhous is a basidiomycete yeast that synthesizes carotenoids, mainly astaxanthin, which are of great commercial interest. Currently, there are many unknown aspects related to regulatory mechanisms on the synthesis of carotenoids in this yeast. Our recent studies showed that changes in sterol levels and composition resulted in upregulation of genes in the mevalonate pathway required for the synthesis of carotenoid precursors, leading to increased production of these pigments. Sterol Regulatory Element-Binding Proteins (SREBP), called Sre1 in yeast, are conserved transcriptional regulators of sterol homeostasis and other cellular processes. Given the results linking sterols and carotenoids, we investigated the role of SREBP in sterol and carotenoid synthesis in X. dendrorhous. In this study, we present the identification and functional characterization of the X. dendrorhous SRE1 gene, which encodes the transcription factor Sre1. The deduced protein has the characteristic features of SREBP/Sre1 and binds to consensus DNA sequences in vitro. RNA-seq analysis and chromatin-immunoprecipitation experiments showed that genes of the mevalonate pathway and ergosterol biosynthesis are directly regulated by Sre1. The sre1- mutation reduced sterol and carotenoid production in X. dendrorhous, and expression of the Sre1 N-terminal domain (Sre1N) increased carotenoid production more than 2-fold compared to wild-type. Overall, our results indicate that in X. dendrorhous transcriptional regulation of genes in the mevalonate pathway control production of the isoprenoid derivatives, carotenoids and sterol. Our results provide new insights into the conserved regulatory functions of SREBP/Sre1 and identify pointing to the SREBP pathway as a potential target to enhance carotenoid production in X. dendrorhous.